Effects of Selenium as a Dietary Source on Performance, Inflammation, Cell Damage, and Reproduction of Livestock Induced by Heat Stress: A Review - Zheng, Yuhui; Xie, Tian; Li, Shengli; Wang, Wei; Wang, Yajing; Cao, Zhijun; Yang, Hongjian (Frontiers in Immunology, 2022)
Heat stress as a result of global warming has harmful consequences for livestock and is thus becoming an urgent issue for animal husbandry worldwide. Ruminants, growing pigs, and poultry are very susceptible to heat stress because of their fast growth, rapid metabolism, high production levels, and sensitivity to temperature. Heat stress compromises the efficiency of animal husbandry by affecting performance, gastrointestinal health, reproductive physiology, and causing cell damage. Selenium is an essential nutritional trace element for livestock production, which acts as a structural component in at least 25 selenoproteins (SELs); it is involved in thyroid hormone synthesis, and plays a key role in the antioxidant defense system. Dietary selenium supplementation has been confirmed to support gastrointestinal health, production performance, and reproductive physiology under conditions of heat stress. The underlying mechanisms include the regulation of nutrient digestibility influenced by gastrointestinal microorganisms, antioxidant status, and immunocompetence. Moreover, heat stress damage to the gastrointestinal and mammary barrier is closely related to cell physiological functions, such as the fluidity and stability of cellular membranes, and the inhibition of receptors as well as transmembrane transport protein function. Selenium also plays an important role in inhibiting cell apoptosis and reducing cell inflammatory response induced by heat stress. This review highlights the progress of research regarding the dietary supplementation of selenium in the mitigation of heat stress, addressing its mechanism and explaining the effect of selenium on cell damage caused by heat stress, in order to provide a theoretical reference for the use of selenium to mitigate heat stress in livestock.